PENDIDIKAN ANAK DALAM KELUARGA (Telaah Kitab Haditst Riyadush Shalihin) - Fera Eka Widayanti (Universitas Muhammadiyah Ponorogo, 2020)
Education is very important for life. A person's first education starts from the family, parents have an important role in the education of their children. Islamic education has its own method of educating. This paper discusses the education of children in the family, which aims to determine how important the role of the family is in educating children. The research method used is descriptive qualitative, which describes the various conditions found in the field regarding the education of children in the family. The data sources consisted of the class teacher and a number of guardians of the students in the school. Based on the results of the study, it can be concluded that the education of children in the family has a very important role, because it is the initial capital for the formation of children's character. Parents as Al qudwah To be good role models. Parents as Al 'adah provide good habits. Parents as Al mau'idhah provide understanding to children. Parents as Al Mulahadhah pay attention to children's potential. Parents as Al 'uqubah give punishment